Preventive Effect of Bifidobacterium Supplementation on Neonatal Cholestasis in Preterm Neonates with Very Low Birth Weight - Gaohong Wu; Xiaoqian Chen; Ningxun Cui; Yunxia He; Jiaying Fan; Dongya Yan; Xueping Zhu; Xiaoli Zhu (Gastroenterology Research and Practice)
Background. Cholestasis is a common but serious clinical condition in preterm neonates. The current management for preterm neonatal cholestasis has limitations. The aim of this study was to determine effects of Bifidobacterium supplementation on the prevention and alleviation of cholestasis in preterm infants with very low birth weight. Methods. Preterm neonates with very low birth weight were enrolled in the Children’s Hospital of Soochow University between December 2012 and December 2017. The patients were randomly assigned into Bifidobacterium and control groups, and effects of Bifidobacterium supplementation on the outcomes were compared between the two groups. Results. There was no significant difference in the baseline characteristics in the two groups. Notably, the proportion of cases with neonatal cholestasis was significantly lower, with fewer neonatal cholestasis-associated complications in the Bifidobacterium group compared with the control group (6% versus 22%, P<0.01). Furthermore, the Bifidobacterium group exhibited less severe cholestasis and better improvement of the liver function than the control group as evidenced by the biochemical tests (P<0.05). Finally, comparison of the other outcomes revealed that significant shorter duration of hospitalization (14.45±2.13 versus 16.12±2.22 days, P<0.01), fewer days to reach the full enteral feeding (9.2±2.11 versus 12±5.67 days, P<0.01), shorter duration of meconium passage (5.0±3.6 versus 6.6±3.38 days, P<0.05), lower proportion of cases on fasting and duration of fasting (0.8% versus 5.6%, P<0.05 and 3.0±1.6 versus 5.6±2.38 days, P<0.01, respectively), and shorter duration of weight gain to normal (4.77±2.49 versus 6.87±2.71 days, P<0.01) in the Bifidobacterium group versus the control group. Conclusions. Bifidobacterium supplementation has significantly preventive and other beneficial effects on the management of cholestasis in preterm infants with very low birth weight. Its long-term safety and effectiveness will need further investigation. This trial is registered with the Chinese Clinical Trial Registry (Registration No. ChiCTR1900022296).